THE WASHINGTON COUNTY GROWTH AND CONSERVATION ACT OF 2006: EVALUATING A NEW PARADIGM IN LEGISLATED LAND EXCHANGES (Utah Environmental Law Review, 2009)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} To say that the proposed Washington County Growth and Conservation Act of 2006 ("Growth Act") was a controversial piece of legislation would be an understatement of considerable magnitude. Though the Growth Act's full title contained nothing likely to generate controversy-it claimed the act was intended to "establish wilderness areas, promote conservation, improve public land, and provide for high quality economic development in Washington County, Utah, and for other purposes" -critics were not mollified by the bill's innocuous-sounding name. Local critics like Southern Utah Wilderness Alliance Executive Director Scott Groene called the bill "a miserable piece of legislation," and editorials in local newspapers attacked the bill's sponsors, Republican Senator Bob Bennett and Democratic Congressman Jim Matheson, both from Utah, as "misguided." The local chapter of the Sierra Club decried the bill as "woefully inadequate." Some municipalities within Washington County even passed resolutions opposing the bill. Supporters, on the other hand, were enthusiastic about what the bill Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 would accomplish. Beaver County, Utah, Commissioner Mark Whitney called the bill a "landmark" and "a great model for how to deal with public lands."